Dung beetle fauna from Mount Mabu, Mozambique. Part 3: A new species of Proagoderus van Lansberge, 1883 with an annotated checklist of the Proagoderus dives (Harold, 1877) species-group (Coleoptera: Scarabaeidae: Scarabaeinae) - Daniel, Gimo M.; Josso, Jean-François; Nganhane, Isildo De N.; Strümpher, Werner P. (Zootaxa, 2024)
A new species of dung beetle, Proagoderus mabuensis Daniel, Josso, Nganhane & Strümpher, new species from Mount Mabu, northern Mozambique, is described, diagnosed, and illustrated. We provide a morphological comparison between the new species and a similar species from Mount Namuli, Mozambique, Proagoderus camiadei Josso, 2014. Both species belong to the Proagoderus dives (Harold, 1877) species-group. Furthermore, we provide an updated checklist of all known members of the dives species-group.